Comparative study of the shape-dependent electrocatalytic activity of platinum multipods, discs, and hexagons: applications for fuel cells - Subhramannia, Mahima; Ramalyan, Kannan; Pillal, Vijayamohanan K. (Langmuir, 2008)
We here demonstrate a remarkable potential-dependent morphological evolution of platinum mesostructures in the form of multipods, discs, and hexagons using a porous anodic alumina membrane (PAAM). These structures prepared potentiostatically at -0.7, -0.5 and -0.3 V, respectively, reveal unique shape-dependent electrocatalytic activity toward both formic acid and ethanol oxidation reactions. A comparison of the electrooxidation kinetics of these structures illustrates that hexagons show better performance toward formic acid oxidation whereas, for ethanol oxidation, multipods show significantly enhanced activity. Interestingly, the enhancement factor (R) for these mesostructures with respect to that of commercial platinized carbon toward formic acid oxidation ranges up to 2000% for hexagons whereas for multipods and disc they are about 700% and 300%, respectively. Similarly, for ethanol oxidation, the calculated value of R varies up to 600% for multipods while for disc and hexagons these values are 500% and 200%, respectively. These shape-dependent electrocatalytic activity of Pt mesostructures have been further correlated with XRD results. Thus, the present results demonstrate the importance of precise control of morphology by an electric field and their potential benefits especially for fuel cell applications since designing a better electrocatalyst for many fuel cell reactions continues to be an important challenge.